Facile and Scalable Route to Access Rare Deoxy Amino Sugars for Nonulosonic Acid Aldolase Biosynthesis - Zhou, Yixuan; Liao, Kuo-Shiang; Li, Shiou-Ting; Wu, Chung-Yi (Frontiers in Chemistry, 2022)
We presented a facile and scalable route for the synthesis of di-azido sugars via one-pot double inversion of the mono-benzoyl sugars by TBAN3 and studied the dependency pattern between solvent and protecting groups as well as the configuration of the neighboring and leaving groups. Moreover, we developed a chemical synthetic strategy for pseudaminic acid precursors (11 steps in 49%). Furthermore, we discussed the configuration of nonulosonic acid precursors for specificity of PseI and PmNanA enzymatic synthesis, permitting us to synthesize new nonulosonic acid derivatives for accessing Pse isomers.